Analisis Kreativitas Siswa dalam Membuat Poster Persuasif melalui Media Canva dengan Model Pembelajaran PJBL pada Siswa Kelas 6C SDN Kauman 1 Kota Malang - Zahroh, Rini; Restian, Arina; Ismanto, Puguh (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze students' creativity in making persuasive posters using the Canva application through the application of project-based learning (PJBL) models. The subjects of the study were 28 students of class 6C of SDN Kauman 1 Malang City. This study focuses on the development of creative thinking skills, digital literacy, and the ability to convey persuasive messages through visual media. The study used a qualitative approach with data collection techniques in the form of observation of the learning process, analysis of poster products produced by students, and interviews with students. The results of the study showed that the implementation of PJBL effectively encouraged increased student creativity, which was reflected in aspects of design uniqueness, clarity and strength of persuasive messages, and attractive visual aesthetics. In addition, the use of the Canva application as a digital media also strengthened students' technological literacy and creativity in the context of 21st century learning. These findings provide important implications for designing innovative learning strategies that combine technology and constructivist approaches, in order to foster students' essential competencies holistically.